The lean-agile way unleash business results in the digital era with value stream management - Rupp, Cecil; Knaster, Richard; Shalloway, Al; Pereira, Steve (Packt Publishing Limited, 2024)
Discover how mastering Lean, Agile, and VSM principles and practices can enhance your product delivery performance, mitigate risk, and foster business agility, giving you a competitive edgeKey FeaturesLearn how to apply Lean practices to eliminate waste and delays, ensuring value for your customersMaster Agile practices to address problems and create value-centric products and servicesExplore VSM methods and tools to identify and prioritize improvement opportunities that maximize value additionPurchase of the print or Kindle book includes a free PDF eBookBook DescriptionIn the fast-paced business and IT landscape, efficiency is key to success. To excel in delivering value to customers, reducing waste, and resolving pain points, identifying the right tools and strategies is paramount. Unlocking the secrets of Lean, Agile, Value Stream Management (VSM), and various digital enhancements, this book offers a roadmap to optimize processes, improve products, and elevate service delivery.
Keywords: Agile software development; Information technology projects / Management; Information technology / Management; Méthodes agiles (Développement de logiciels); Projets de technologie de l'information / Gestion; Technologie de l'information / Gestion; BUSINESS & ECONOMICS / Strategic Planning